Corporate governance code and voluntary disclosure of integrated reporting: Evidence from an emerging economy - Hamad, S. (John Wiley and Sons Ltd, 2022)
Integrated reporting (IR) is the most recent business reporting paradigm that seeks to improve information quality and create sustainable value. This study investigates the impact of the Malaysian Code on Corporate Governance (MCCG) 2017 on the voluntary IR disclosure quality. Data is collected from the top 100 Malaysian public listed companies from 2016 to 2020. The study used content analysis and a developed IR disclosure index on panel data of companies that fully adopt IR. The results show ongoing growth in IR adoption among Malaysian companies; most of them are aware of its benefits. The study provides empirical evidence on the positive influence of MCCG 2017 on the IR disclosure quality using the random effects generalised least squares regression model. The trend analysis confirms that Malaysian companies enhanced their IR disclosure quality, especially after 2017. The results also show that the research sample has reported 70 for each IR content element in 2020. In this regard, the highest reported element is ârisks and opportunitiesâ. Thus, several companies have established enterprise risk management frameworks and risk committees. This study contributes to the literature by providing an intensive investigation of the IR practices in Malaysia's earliest adoption stages preceding and following the MCCG 2017. Â© 2022 ERP Environment and John Wiley & Sons Ltd.